Influence of drying method and location on amino acids and mineral elements of Sternocera orissa Buguet 1836 (Coleoptera: Buprestidae) in South Africa - Kagiso, G.S.; Maboko, S.M.; Phatu, W.M. (Academic Journals, 2012)
Influence of drying method and location on amino acid and mineral composition of African metallic wood boring beetle, Sternocera orissa Buquet (Coleoptera: Buprestidae), widely consumed in certain rural communities of Limpopo Province, South Africa was investigated. Randomised complete block design in a 3 × 3 factorial arrangement was used with three drying methods (oven-drying, freeze drying, locally method) and three locations (Khureng, Magatle, Ga-Masemola). The experiment was replicated three times. Relative to freeze-drying, oven-drying and cooking significantly increased essential and non-essential amino acids. Location did not have significant effect on the essential and non-essential amino acids of S. orissa across all the villages. Similarly, oven-drying and cooking increased potassium, phosphorus, iron, zinc and magnesium. Compared to locations, beetlesat Ga-Masemola had high amount of iron. Results of this study suggest that oven-drying and cooking improved the amino acids and mineral composition of S. orissa, which has the potential of enhancing nutrition nationally and internationally.